Sartorial insurgencies: Rebel women, headwraps and the revolutionary Black Atlantic. Issue 1 (2nd January 2022) - Willson, Nicole
ABSTRACT: This study interrogates the trope of the "tropical temptress" that dominated colonial print culture. Encoded in textual accounts reliant on this trope, it posits, is a subtextual fear of Black female agency. To excavate and rehabilitate the voices of women that have been both occluded and co-opted by the colonialist archive, it recognises a need to look beyond. It takes its cue from Danielle Skeehan, who seeks out traces of Black female insurgency in "extra-discursive and material texts, " privileging the material transcripts that bear unique witness to Black women's experiences in the age of slavery. Focusing on the symbolic importance of Afro-Creole headwraps within the revolutionary Black Atlantic and, in particular, within the context of revolutionary Saint-Domingue, it shows how women of colour in the colonial circum-Caribbean authored their own powerful revolutionary counternarratives to colonial dominance through acts of creativity, ingenuity and domestic labour.